Response of Cabbage Seedlings to Different Sources of Arbuscular Mycorrhiza (Bangladesh Journal of Microbiology, 2016)
The effect of different sources of Arbuscular mycorrhiza (AM) fungi on cabbage seedlings (Atlas-70) were conducted. Eight sources of AM fungi viz. Jessore (AM-01), Rahmatpur (AM-02), Joydebpur (AM-03), Ullapara (AM-04), Jamalpur (AM-05), Hathazari (AM-06), Ishurdi (AM-07), Rajshahi (AM-08) from different AEZs of Bangladesh were studied along with a control and mixed sources on cabbage seedlings. Soil based AM inoculum at the rate of 2.0 kg m-2 was used. Biomass yield of cabbage (Atlas-70) increased from 28.0% to 130.7% in 2007-08 and 44.8% to 96.9% in 2008-09 over control by inoculation with different sources of AM. The highest biomass yield (503 mg seedling-1 in 2007-08 and 321 mg seedling-1 in 2008-09) of cabbage was observed with Jamalpur source which was identical to all AM source except Ishurdi source in 2007-08 and with Joydebpur source which was identical to all Jamalpur source in 2008-09. Uptake of all the nutrients by cabbage seedlings was also improved by inoculation with AM fungi. The AM fungi from all the sources appeared to be effective in enhancing the growth and development of cabbage seedlings.Bangladesh J Microbiol, Volume 29, Number 2, Dec 2012, pp 90-96